Motivasi Penggunaan Kesenian Tradisional dalam Dakwah Islam - Nabillah, Gina; Junaedi, Jujun; Fatoni , Uwes (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This research is to determine the achievemnt motivation, power and affiliation of the Daway Group to preach using the traditional art of wayang golek. The research method used is descriptive qualitative using Needs Theory by David McClelland (1960). The research results showed that the Daway Group’s motivation to achieve achievements was triggered by the desire to receive awards in the aspects of cultural preservation, becoming a professional group and developing business. Then, the Daway Group’s motivation to have power was triggered by the desire to have popularity and religious authority. And finally, the Daway Group’s motivation to have an affiliation was triggered by the desire to have an identity and the desire to develop a community.